METODE PENENTUAN ARAH KIBLAT MASJID DARUNNA'IM KOTA PONTIANAK - Muhammad Zikrurrahman (Al-Maslahah : Jurnal Ilmu Syariah, 2020)
Abstract Facing the qibla direction is one of the requirements of performing prayer, and therefore of course it must be made as accurate as possible in the direction of the Kaaba. Darunna’im Mosque is the center of religious worship services for students in the Darunna’im Islamic Boarding School in Pontianak. From the search results using the Google Earth application, the researcher found inaccuracy of the direction of the mosque building from what i should be which is 292° 44’ 56” while the direction of the mosque building qibla is 281° 50’ 00” so there is a deviation of 10° 54’ 56”. From the above background, the researcher felt the need to explore further the direction of the mosque’s qibla with the focus of research namely on the methods carried out in deternmining the direction of the Darunna’im mosque’s qibla and accuracy of the direction of the mosque by using several methods of determining the qibla direction (Qibla with Theodolite, Compass and Rashdul qibla). This study uses a descriptive method with a qualitative approach, and techniques of interview, direct observation, and field measurements. Data were obtained as material for analysis. After the analysis was done, than the researcher drew conclusions and provided suggestions. From the result of the analysis of the data that the researcher got in the field, it can be concluded that the direction of the Darunna’im Mosque was deviated. The measurementsof the mosque’s qibla direction using Google Earth shows the direction of 292° 44’ 56” while the direction of the mosque is 281° 50’ 00”, a deviation of 10° 54’ 56” occurs. Then using theodolite on May 28, 2019 at 16:19 WIB showing the direction of 0° 1’ 16.62” while the direction of the Mosque is 349° 07’ 32.76”, then a deviation of 10° 53’ 43.86” occurs. Then on July 16 using theodolite , it showed the direction 0° 1’ 28.76” while the direction of the Mosque is 349° 07’ 44.9”, then there is a deviation of 10° 53’ 43.86”. Then when the Rashdul Qibla was used on May 28, 2019, it showed at 16:17 WIB. Then at the time of Rashdul Qibla on July 16, it showed the qibla direction at 16:26 WIB. Then using Compass, it showed the direction 292° 44’ 56.21” while the direction of the mosque is 281° 50’ 00”, so a deviation of 10° 54’ 56.21” occurs. Keywords: Qibla Direction, Accuracy, and Darunna’im Mosque.